2022
DOI: 10.1186/s12920-022-01252-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of the tissue infiltrated and peripheral blood immune cell subsets with response to radiotherapy for rectal cancer

Abstract: Background Tumor microenvironment plays pivotal roles in carcinogenesis, cancer development and metastasis. Composition of cancer immune cell subsets can be inferred by deconvolution of gene expression profile accurately. Compositions of the cell types in cancer microenvironment including cancer infiltrating immune and stromal cells have been reported to be associated with the cancer outcomes markers for cancer prognosis. However, rare studies have been reported on their association with the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…In recent years, more attention has been paid to the immune genes related to RC, and their effect on radiosensitivity and prognosis. Immune genes are associated with immune regulation and microenvironment of the tumors, the expression of which can affect patients' response to radiotherapy[8, 9,10].In this study, we established and validated a prognostic risk model based on four RRIGs (BMP2, COLEC10, MASP2, GCGR), the model can serve as an independent prognostic factor and has potential value in predicting the prognosis of RC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, more attention has been paid to the immune genes related to RC, and their effect on radiosensitivity and prognosis. Immune genes are associated with immune regulation and microenvironment of the tumors, the expression of which can affect patients' response to radiotherapy[8, 9,10].In this study, we established and validated a prognostic risk model based on four RRIGs (BMP2, COLEC10, MASP2, GCGR), the model can serve as an independent prognostic factor and has potential value in predicting the prognosis of RC patients.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were consistent with that of some previous studies. [33][34][35] Nevertheless, these preliminary results still require confirmation in a larger population. Furthermore, it is important to thoroughly analyze the consistency of the immune cell subset compositions between peripheral blood and tumor microenvironment, as well as the specific status and function of T cell subsets.…”
Section: Open Accessmentioning
confidence: 93%
“…Another study by Napolitano et al suggested that an abundance of FOXP3+ regulatory T-cells after CRT was linked with the poor response of rectal tumors [153]. In contrast, Zhu et al found that high levels of CD4+ circulating T-cells were correlated with better tumor response to RT and better prognosis [154].…”
Section: Systemic Immune Responsementioning
confidence: 99%